2019
DOI: 10.1002/pssa.201800749
|View full text |Cite
|
Sign up to set email alerts
|

Polycrystalline SnO2 Visible‐Light‐Transparent CO2 Sensor Integrated with NiO/ZnO Solar Cell for Self‐Powered Devices

Abstract: Monolithic visible‐light‐transparent carbon dioxide (CO2) sensor/solar cell‐integrated devices are fabricated using RF sputtering. The optical transmittance of the integrated device in the visible region is found to be over 60%. The solar cell is composed of p‐type NiO and n‐type ZnO layers, and exhibits small but noticeable photovoltaic effect under illumination. The CO2 sensor layer is made from LaOCl/SnO2 layers, and its resistance varies when electrical power is supplied from an external power source. XPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…This work gives a general idea of the integrated gas sensor and solar cell. Ryo Tanuma et al [77] fabricated an integrated CO 2 sensor and solar cell based on the similar idea. The solar cell comprised a p-NiO:Li/n-ZnO heterojunction structure, and as for CO 2 gas sensing, thin layers of LaOCl/SnO 2 were deposited.…”
Section: A Integrated Gas Sensor and Solar Cellmentioning
confidence: 99%
“…This work gives a general idea of the integrated gas sensor and solar cell. Ryo Tanuma et al [77] fabricated an integrated CO 2 sensor and solar cell based on the similar idea. The solar cell comprised a p-NiO:Li/n-ZnO heterojunction structure, and as for CO 2 gas sensing, thin layers of LaOCl/SnO 2 were deposited.…”
Section: A Integrated Gas Sensor and Solar Cellmentioning
confidence: 99%
“…Among them, NiO/ ZnO solar cells composed of p-type Li-doped NiO (NiO) and n-type ZnO have many benefits. [1][2][3][4][5][6] The NiO/ZnO solar cells only absorb the ultraviolet (UV) light and transmit visible light. Therefore, they can be used in various ways; for instance, in greenhouse panels, in UV blocking windows and in designed surface, and to supply power to low power consumption devices developed in recent years, such as temperature 7,8) and medical 9,10) sensors.…”
mentioning
confidence: 99%
“…With the combination of a visible-light-transparent solar cell and a transparent device, monolithic self-powered "invisible Internet of Things devices" will be feasible. 5) In addition, the NiO/ZnO solar cells have the potential to possess high tolerance against environmental heat, radiation, and UV light. In general, semiconductors with a wide-bandgap possess high electrical, thermal, and radiation stability.…”
mentioning
confidence: 99%
“…The merit of the photovoltaic self-powered gas sensor lies in its low energy consumption, as it can absorb energy from illuminated light and then drive itself or other miniaturized devices without external energy sources. For instance, Tanuma and Sugiyama 162 fabricated a NiO/ZnO p-n heterojunction as a solar cell to activate a polycrystalline SnO 2 -based CO 2 sensor. Gad et al 74 reported a photovoltaic self-powered gas sensor based on a Si/ZnO@CdS p-n heterojunction, as demonstrated in Fig.…”
Section: Three Typical Device Structures and Relevant Sensing Mechanismsmentioning
confidence: 99%